Selection of optimal ripening stage of papaya fruit (Carica papaya L.) and vacuum frying conditions for chips making - Soto Retana, Marvin (2021)
The aim of this study was to compare the physicochemical characteristics of papaya fruits from Costa Rica (Carica papaya L. cv Pococí) and vacuum-fried chips obtained from these fruits at three different postharvest ripening stages (RS3, RS4, and RS5) and select the optimal stage for vacuum frying. In addition, response surface methodology was used to optimize vacuum frying conditions (temperature and time) to obtain papaya chips with desirable characteristics. RS4 was found the most adequate ripening stage for processing papaya fruits to obtain vacuum-fried chips with suitable physicochemical characteristics and good sensory acceptance. The optimal vacuum frying conditions at 25 kPa were: 120 °C and 13.1 min. Vacuum frying caused 40 and 60% degradation of β-carotene and β-cryptoxanthin, respectively, and a 1.5-fold increase in the extractability of lycopene. The total carotenoid content of the vacuum-fried papaya chips was 381 mg/kg chips fresh weight.